Crack growth study under thermo-mechanical loads: parametric analysis for 2024 T3 aluminum alloy - Salmi abdallah; Mohamed Elajrami; Mohamed El-Amine Slimani (Fracture and Structural Integrity)
Due to their severe operating conditions, many industrial components are subjected to complex combinations of cyclic mechanical stresses and thermal pressures. These combinations are responsible for the initiation and propagation of fatigue cracks in these parts, which can lead to failure. Thus, the study of the fatigue strength of these parts in such conditions becomes essential because it allows us to predict the life and safety of components.